The impact of institutions on innovation networks: empirical evidence from Poland - Godlewska, Małgorzata; Banasik, Przemysław; Morawska, Sylwia (Technological and Economic Development of Economy, 2022)
Innovation networks may accelerate and improve the innovation process, while institutional pathologies may hamper it. This study employs the Kruskal-Wallis H test and regression analysis to determine if the relationship between institutions and innovation networks does exist among the investigated variables. The purpose of the study was to find out whether cooperation with special local institutions influences the innovative behaviour of local governments manifested by participation in innovation networks or innovation networks based on formal institutions limit institutional pathologies better than informal ones. Current paper presents results of an empirical study conducted through survey among all local governments in Poland. The findings show that previous cooperation with special local institutions influences the innovation behaviour of local governments or innovation networks based on formal rules limit the institutional pathologies of innovation networks better than those based on sanctions, common values, codes of ethics, governance codes or culture. The investigated problem is significant, as properly functioning innovation networks may generate incremental innovations, which may help to solve the contemporary challenges. The practical implications for national regulatory bodies highlight the need for an enforcement mechanism which may support the formalisation of innovation networks.